Enhanced performance of 19 single gate MOSFET with high permittivity dielectric material - Ameer F. Roslan; F. Salehuddin; A. S. M. Zain; K. E. Kaharudin; I. Ahmad (Institute of Advanced Engineering and Science, 2020)
In this research, the performance of the 19 nm single gate MOSFET is enhanced through the implementation of the high permittivity dielectric material. The MOSFET scaling trends necessities in device dimensions can be satisfied through the implementation of the high-K dielectric materials in place of the SiO2. Therefore, the 19 nm n-channel MOSFET device with different High-K dielectric materials are implemented and its performance improvement has also been analysed. Virtual fabrication is exercised through ATHENA module from Silvaco TCAD tool. Meanwhile, the device characteristic was utilized by using an ATLAS module. The aforementioned materials have also been simulated and compared with the conventional gate oxide SiO2 for the same structure. At the end, the results have proved that Titanium oxide (TiO2) device is the best dielectric material with a combination of metal gate Tungsten Silicides (WSix). The drive current (ION) of this device (WSix/TiO2) is 587.6 µA/um at 0.534 V of threshold voltage (VTH) as opposed to the targeted 0.530 V predicted, as well as a relatively low IOFF that is obtained at 1.92 pA/µm. This ION value meets the minimum requirement predicted by International Technology Roadmap for Semiconductor (ITRS) 2013 prediction for low performance (LP) technology.